2012
DOI: 10.5402/2012/628317
|View full text |Cite
|
Sign up to set email alerts
|

What Really Causes Necrotising Enterocolitis?

Abstract: Background. One of the most serious gastrointestinal disorders occurring in neonates is necrotising enterocolitis (NEC). It is recognised as the most common intra-abdominal emergency and is the leading cause of short bowel syndrome. With extremely high mortality and morbidity, this enigmatic disease remains a challenge for neonatologists around the world as its definite aetiology has yet to be determined. As current medical knowledge stands, there is no single well-defined cause of NEC. Instead, there are near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 101 publications
2
21
0
8
Order By: Relevance
“…Because its etiology has not been identified yet, this illness continues to be a hardship for neonatologists in the world due to its extremely high mortality and morbidity rates. [1][2][3] The high increase in the NEC incidence has been associated with two factors. The first one is the increase in the preterm labors with cesarean sections.…”
Section: Introductionmentioning
confidence: 99%
“…Because its etiology has not been identified yet, this illness continues to be a hardship for neonatologists in the world due to its extremely high mortality and morbidity rates. [1][2][3] The high increase in the NEC incidence has been associated with two factors. The first one is the increase in the preterm labors with cesarean sections.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that the patients in NEC group were prone to develop PDA and IVH, even though the proportion of preterm births was similar between the NEC group and matched controls. PDA, hypoxia, and hypotension have been identified as risk factors for NEC and IVH (25,26), and these factors are commonly responsible for circulatory instability or ischemic and hypoxic injury. IVH is considered to be a predictor of neurodevelopmental outcomes in preterm infants (27).…”
Section: Discussionmentioning
confidence: 99%
“…Though IP is high at birth in preterm infants, it rapidly decreases over the first few days, which is associated with diminished risks for adverse outcomes 16,30 . Aberrant intestinal barrier function manifests by persistently high and/or late decrease in IP and is likely due to the physiological immaturity of the GI tract barrier function and altered levels of the normal microbial communities 14,15 , resulting in microbial invasion of the intestinal wall and gut lamina propria triggering a cascading inflammatory response and ultimately intestinal necrosis and severe infection 2 . Multiple studies have revealed microbial community dysbiosis is involved in stimulating a hyperinflammatory response that leads to NEC 25,26,28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…In this condition, bacteria across the intestinal wall leading to local and systemic infection and inflammation, and bowel wall necrosis and perforation. Intestinal barrier immaturity, characterized as elevated intestinal permeability (IP), or “leaky gut”, is the proximate cause of susceptibility to NEC in preterm neonates 14,15 . It is critical to characterize the preterm infant intestinal microbiota to identify dysbiotic states associated with increased intestinal leakiness, as well as beneficial bacteria associated with improved intestinal barrier function, for subsequent stratification of early diagnosis, early intervention and primary prevention of leaky gut and its sequelae.…”
Section: Introductionmentioning
confidence: 99%